Effect of alcohol on some physiological and biochemicall varies in the blood of alcoholics - Mahmoud Ismael Aljbouri (College of Education for Pure Sciences, 2009)
This study was conducted to determine the effect of alcohol dduct on some of blood parameters and biochemical activities. there for fourty blood samples from anormal and alcohol addicted healthy males Then they were compared with (20) blood samples collected from anon-alcohclic healthy persons as a contral group. Results show a significent increase in the concentration of Hb and PCV in all (3) groups as compared with control group. There were a significent decrease in the concentration of total protein in (3) groups acompared with the a control group, while the blood urea increased significantly as compared with the control group and the results revealed also significent increase in the enzyme of transaminases (Alanine amino transferase ALT and aspartate aminotransferase AST) as compared with the control group.